Unveiling the Potential of Gut Microbiota: Promising Approaches to Treat Drug-Resistant Epilepsy - Domańska, Natalia; Bojarska, Małgorzata; Bogucka, Julia; Brzyska, Anna; Kosowska, Michalina; Piecewicz-Szczęsna, Halina (Quality in Sport, 2024)
Introduction: Epilepsy is a chronic, non-infectious disease of the brain. Data shows that even 70 million people worldwide suffer from it and one-third of them fail to control it with anti-epileptic drugs. The gut microbiota has an impact on the course of the disease. The microbiota mediates between the gastrointestinal system and the central nervous system. Purpose: The aim of the work is to analyse how modification of the gut microbiota affects patients with drug-resistant epilepsy. Material and method: In December 2023, an extensive search was conducted and articles found in the Medline (PubMed) databases were selected by using the following keywords: drug-resistant epilepsy, gut microbiota, gut-brain axis, ketogenic diet, probiotics, faecal microbiota transplantation, to focus on recent developments and advancements in the field, the search was limited to articles published between 2017 and 2023. Conclusions: The intestinal microbiota in drug-resistant epilepsy (DRE) patients differs from that of healthy individuals or drug-sensitive epilepsy patients. Acknowledging the presence of the gut-brain axis and its impact on the central nervous system, we can view altering the flora as a potential therapeutic approach for DRE patients. The ways in which microbiota changes have been confirmed by research include: ketogenic diet, antibiotics, probiotics and fecal microbiota transplantation (FMT). Modifying the microbiota through these mentioned methods is all promising for treating DRE.